Kawasaki Disease in an infant of two months of age - Flores Chávez, Ana María del Pilar (2018)
We present a case of a 2 months old infant with Kawasaki Disease (KD), who had an incomplete clinical presentation at the onset of the disease, as a final complication dilatation of the coronary arteries. An updated review of the literature on this pathology is made. Although this disease is rare in this age group, it is important to think of this disease because early treatment reduces the incidence of cardiac complications. In conclusion, the differential diagnosis of all febrile infants younger than 6 months with no apparent focus should include Kawasaki's disease, thus failing to meet the necessary criteria.